ALA‐mediated biphasic downregulation of α‐7nAchR/HIF‐1α along with mitochondrial stress modulation strategy in mammary gland chemoprevention. Issue 4 (17th September 2018) - Roy, Subhadeep; Singh, Manjari; Sammi, Shreesh Raj; Pandey, Rakesh; Kaithwas, Gaurav
Abstract: The study elucidates the effect of ɑ‐linolenic acid (ALA) on mitochondrial stress, hypoxic cancer microenvironment, and intervention of cholinergic anti‐inflammatory pathway using N ‐methyl‐ N ‐nitrosourea (MNU) induced estrogen receptor (ER+) mammary gland carcinoma and Caenorhabditis elegans model, respectively. The efficacy of ALA was scrutinized in vivo and in vitro using various experiments like hemodynamic studies, morphological analysis, antioxidants parameters, immunoblotting, and quantitative reverse transcription polymerase chain reaction. The effect of ALA was also validated using C. elegans worms. ALA administration had a positive effect on tissue architecture of the malignancy when scrutinized through the whole mount carmine staining, hematoxylin and eosin staining, and scanning electron microscopy. The proteomic and genomic checkpoint revealed the participation of mitochondrial dysfunction, alteration of hypoxic microenvironment, and involvement of cholinergic anti‐inflammatory response after treatment with ALA. ALA treatment has also increased the level of synaptic acetylcholine and acetylcholine esterase with a significant decrease in lipid content. It was concluded that ALA persuaded the mitochondrial stress, activation of downstream cholinergic anti‐inflammatory markers, and favorable regulation of hypoxia microenvironment through inhibition of fatty acid synthase and sterol regulatory element‐binding protein. Abstract : ɑ‐Linolenic acid persuaded the mitochondrial stress, activation of downstream cholinergic anti‐inflammatory markers, and favorable regulation of hypoxia microenvironment through inhibition of fatty acid synthase and sterol regulatory element‐binding protein.